Pengaruh Perbedaan Karakteristik Brand Ambassador terhadap Keputusan Pembelian Konsumen Ruangguru - Andrean Fredy Iswanto; Sanaji Sanaji (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The emergence of Ruangguru, an online-based tutoring application in 2014, has been very intriguing because it defeated several competitors, including Zenius.net, a pioneer of online-based tutoring applications in Indonesia. Ruangguru uses several Brand ambassadors and Celebrity Endorsers to support their brands with differences in professional and characteristic fields. This study examines whether there are differences in the influence of several brand ambassadors from Ruangguru with different characteristics/professions towards purchasing decisions. This study uses 200 samples with non-probability sampling techniques, and the method used is judgmental sampling. The data collection method uses questionnaires online. The data analysis technique used in this study is Regression and ANOVA. The result is that the differences in Ruangguru brand ambassadors' average influence on consumer and professional purchasing decisions increase significant differences,